2019
DOI: 10.1186/s13030-019-0144-5
|View full text |Cite
|
Sign up to set email alerts
|

Bio-psychosocial factors of children and adolescents with internet gaming disorder: a systematic review

Abstract: Previous large-scale studies suggest that internet gaming disorder (IGD) among children and adolescents has become an important public concern. Minors are known to be particularly susceptible to problematic internet gaming use owing to age-related underdevelopment of cognitive control. It has been shown that precursors of addictions appear during adolescence; therefore, prevention efforts must be established targeting minors who have their first experience with addictive substances and behaviors during pubesce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
98
0
8

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(113 citation statements)
references
References 94 publications
(126 reference statements)
7
98
0
8
Order By: Relevance
“…Similar to substance use, fulfilling some addiction criteria might indicate extensive usage or a kind of normative behavior rather than pathology [24]. In line with this, Sugaya et al (2019) revealed that some IGD criteria are more common in children and adolescents than others, which supports the suggestion of Colder Carras and Kardefelt-Winter (2018) to classify DSM-5 criteria in "weak" and "strong" symptoms of pathological gaming [4,24].…”
Section: Introductionsupporting
confidence: 77%
See 3 more Smart Citations
“…Similar to substance use, fulfilling some addiction criteria might indicate extensive usage or a kind of normative behavior rather than pathology [24]. In line with this, Sugaya et al (2019) revealed that some IGD criteria are more common in children and adolescents than others, which supports the suggestion of Colder Carras and Kardefelt-Winter (2018) to classify DSM-5 criteria in "weak" and "strong" symptoms of pathological gaming [4,24].…”
Section: Introductionsupporting
confidence: 77%
“…Children and adolescents are especially prone to engage in pathological gaming, as their capabilities of cognitive control are still under development [1][2][3]. Sleep disorders, deterioration of school grades, and family conflicts, as well as emotional, behavioral, and cognitive problems, are more common among young pathological gamers than among non-and normal-gaming peers [4]. Moreover, emotional dysregulation (ED) as a hallmark of psychopathology is associated with pathological gaming behavior in children and adolescents [5,6].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another review classified effect sizes as small, medium, or large and presented a table of counts of effect sizes for four mental health outcomes as a way to address heterogeneity in measurement [ 28 ]. Most reviews discussed limitations at the study, outcome, and review level, but two reviews did not discuss limitations systematically [ 27 , 29 ].…”
Section: Resultsmentioning
confidence: 99%